Evaluation of the Competency Improvement Program for Teachers of Students with Intellectual Disabilities in Reproductive Health Education - Sri Roswati; Amelia Vinayastri; Ermawati Ermawati (Department of Special Education, 2025)
This study evaluates the implementation quality of the Special Education Teacher Competency Improvement Program in Reproductive Health Education organized by the Ministry of Education, Culture, Research, and Technology. Using the Kirkpatrick evaluation model, the study examines four levels: participant reactions, learning outcomes, behavioral changes, and program results. A mixed-methods approach was employed, involving questionnaires, interviews, classroom observations, analysis of student learning outcomes, and program documentation. Participants included 9 master teachers and 42 partner teachers. The findings indicate high levels of teacher enthusiasm and satisfaction, with training materials perceived as relevant and practical. Significant improvements were observed in teachers’ knowledge, attitudes, and instructional skills, accompanied by observable changes in classroom practices, including lesson planning, assessment, and the use of contextual learning media. The program positively impacted students with intellectual disabilities by enhancing understanding, learning motivation, and self-protection skills. It also strengthened collaboration among teachers, parents, school leaders, and health professionals. Overall, the program was systematically designed, responsive to teachers’ needs, and underscores the importance of sustained mentoring and the strategic role of master teachers in ensuring program sustainability